2004
DOI: 10.1002/glia.20054
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally–derived olfactory ensheathing cells do not promote primary afferent regeneration following dorsal root injury

Abstract: Olfactory ensheathing cells (OECs) may support axonal regrowth, and thus might be a viable treatment for spinal cord injury (SCI); however, peripherally-derived OECs remain untested in most animal models of SCI. We have transplanted OECs from the lamina propria (LP) of mice expressing green fluorescent protein (GFP) in all cell types into immunosuppressed rats with cervical or lumbar dorsal root injuries. LP-OECs were deposited into either the dorsal root ganglion (DRG), intact or injured dorsal roots, or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 75 publications
1
40
0
1
Order By: Relevance
“…A computerized program provided average density measurements for each 20-mm segment of the 720-mm long rectangular strip. To quantify CGRP-positive axon density in the spinal cord, we carried an automated thresholding procedure, 31,33,34 which first defines the thickest and brightest regions, and then, following application of a Laplacian omnidirectional edge-detection filter, the finer processes ( Figure 1, bottom). The edge-detection filter effectively normalizes the signal-to-noise ratio such that small variations in immunoreactivity across sections are eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…A computerized program provided average density measurements for each 20-mm segment of the 720-mm long rectangular strip. To quantify CGRP-positive axon density in the spinal cord, we carried an automated thresholding procedure, 31,33,34 which first defines the thickest and brightest regions, and then, following application of a Laplacian omnidirectional edge-detection filter, the finer processes ( Figure 1, bottom). The edge-detection filter effectively normalizes the signal-to-noise ratio such that small variations in immunoreactivity across sections are eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Crush of the dorsolateral funiculus was performed as described previously (Ramer et al, 2004a;Richter et al, 2005). In summary, animals were anesthetized with xylazine/ketamine (10 mg/kg, i.p.…”
Section: Dorsolateral Funiculus Crush and Cell Transplantationmentioning
confidence: 99%
“…Many OEC transplant studies have produced conflicting data regarding the ability of OECs to promote regeneration, even in the same model of SCI (Ramon-Cueto and Nieto-Sampedro, 1994;Ramer et al, 2004a;Riddell et al, 2004). Some of these differences may be attributable to different culture conditions that could change the biology of OECs and how they behave after transplantation (Franklin et al, 1996;Li et al, 1997;RamonCueto et al, 1998;Ramer et al, 2004b).…”
Section: Oecs Promote Drg Neurite Outgrowthmentioning
confidence: 99%
“…[227][228][229] However, recent data from our group and others indicate that OEC transplantation does not support regeneration of sensory axons across the injured DREZ. [230][231][232] Using OECs from the GFP mouse, we have observed that OEC injection into the spinal cord mechanically disrupts the DREZ, permitting sensory axon ingrowth but not functional regeneration involving the re-acquisition of appropriate targets on the other side of the injured DREZ. 232 After SCI, OECs were also applied to remodel a PNS-CNS interface, namely, that established by grafting Schwann cells into CNS tissue.…”
Section: In the Spotlight: Schwann Cells And Oecsmentioning
confidence: 99%
“…[230][231][232] Using OECs from the GFP mouse, we have observed that OEC injection into the spinal cord mechanically disrupts the DREZ, permitting sensory axon ingrowth but not functional regeneration involving the re-acquisition of appropriate targets on the other side of the injured DREZ. 232 After SCI, OECs were also applied to remodel a PNS-CNS interface, namely, that established by grafting Schwann cells into CNS tissue. When OECs were injected into the proximal and distal stumps of transected spinal cord spanning a SC bridge, regenerating axons crossed the graft-host interfaces and reentered the spinal cord.…”
Section: In the Spotlight: Schwann Cells And Oecsmentioning
confidence: 99%